Açaí (Euterpe oleracea) Waste Management: mapping the scientific sroduction from 2011 and 2021 - Rosa, Carla Lorena Sandim da; Silva, Rodrigo Cândido Passos da; Camargo, Plínio Barbosa de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The commercial demand for açaí berry has been steadily increasing, accompanied by a rising generation of açaí residue, whether from agro-industrial processes or local sales in Northern Region cities. This study aimed to investigate the state of scientific research on açaí seed residue over ten years. Bibliometrics was employed to map and identify trends in publications related to the topic between 2011 and 2021. It observed that scientific production on the subject is emerging and continually growing, with contributions from researchers from various parts of Brazil and other countries. Furthermore, the discussion on the subject in well-regarded journals with significant impact factors within the academic community demonstrates its promise and interest for future research, particularly as it aligns with sustainable development guidelines. Additionally, the analysis identified six thematic subareas of published works: renewable energy source, pollutant removal, soil conditioner, extractive source for industries, raw material for the construction sector, and eco-efficient management. Açaí berry seed residue can be reused in various ways and has garnered the attention of both the national and international academic communities.